Mark Twain and metaphor - Bird, John, 1954- (Mark Twain and his circle series., 2007)
"Examines how Twain used metaphor to express his attitudes and thoughts, revealing not only hidden facets of Twain's artistry but also new aspects of works that we think we know well such as The Adventures of Tom Sawyer, Adventures of Huckleberry Finn, and A Connecticut Yankee in King Arthur's Court"--Provided by publisher.